Epidemiology of Pulmonary Tuberculosis in Diabetes Mellitus Patients - Syahputri, Siti Ananda Hardita; Mufida, Diana Chusna; Bumi, Candra (Poltekkes Kemenkes Tanjung Karang, 2023)
Pulmonary Tuberculosis (pulmonary TB) and Type 2 Diabetes Mellitus (DMT2) are the leading causes of death worldwide. The prevalence of T2DM has increased worldwide as an aging result, urbanization, changes in diet, and reduced physical activity patterns, which have increased obesity. Pulmonary TB and T2DM often occur together and complicate each other during treatment. Pulmonary TB infection-DMT2 appears based on a low immunity state. When the body has low immunity, the reactivation of Mycobacterium tuberculosis bacteria can occur more easily. However, several factors can influence it. This study uses a case-control design. The researcher made observations on the subjects by comparing the case group and the control group. This study had 74 respondents in the case group and 74 respondents in the control group using quota sampling. This study has the results that the factors that influence the incidence of pulmonary TB-DMT2 are smoking behavior 0.000Î±, age 0.877>Î±, and alcohol consumption 0.998>Î±. (Î±=0.05). The factor that most influences the risk of pulmonary TB-DMT2 is smoking behavior with a wald value of 13.391. This research provides information regarding the problem of pulmonary TB-DMT2 in Jember. To increase public awareness of the risk for Pulmonary TB-DMT2.